Electroacupuncture improves metabolic and ovarian function in a rat model of polycystic ovary syndrome by decreasing white adipose tissue, increasing brown adipose tissue, and modulating the gut microbiota. Issue 4 (August 2022) - Zhang, Feifei; Ma, Tong; Tong, Xiaoyu; Liu, Yanjun; Cui, Peng; Xu, Xiaoqing; Shi, Jiemei; Hu, Wei; Lu, Wenhan; Pei, Zhenle; Xu, Minzhen; Li, Xin; et al.
Background: Polycystic ovary syndrome (PCOS) affects 8%–15% of reproductive-age women and is associated with reproductive disorders, abdominal obesity, hyperinsulinemia, insulin resistance, type 2 diabetes, and cardiovascular diseases. Acupuncture, as a traditional physical therapy method, could affect various metabolic disorders such as obesity, hyperplasia, gout, and cardiovascular and cerebrovascular diseases in clinical practice. Moreover, electroacupuncture (EA) has been shown to decrease body weight in rats with PCOS; however, the mechanism of weight loss and the relationship between adipose tissue and gut microbiota remain unclear. Objective: To explore the effect and mechanism of EA on white and brown adipose tissues and gut microbiota, and its follow-up effect on reproductive function, in a rat model of PCOS. Methods: Daily EA treatment was administered at ST29 and SP6 in a dihydrotestosterone (DHT)-induced PCOS-like rat model (PCOS + EA group). Effects of EA on in vivo and in vitro adipose volume and weight, organ weight coefficients, body weight, hormonal profiles, and estrous cyclicity were measured, and compared with untreated PCOS model rats (PCOS group) and healthy rats (control group). Microbial DNA was extracted from the fecal samples to analyze group abundance and diversity. Results: EA improved estrous cyclicity, decreased body weight, decreased visceral and subcutaneous fat content, and increased brown adipose tissue weight. EA also normalized serum DHT and progesterone levels and improved glucose tolerance. There were few significant differences in the composition or diversity of the gut microbiota between control, PCOS, and PCOS + EA groups, except for the relative abundances of Tenericutes at the phylum level and Prevotella_9 at the genus level, which were significantly different in the PCOS group before and after EA treatment. Both are important microflora, strongly related to body weight. Conclusion: EA regulated the metabolic disorders and improved reproductive function in this PCOS-like rat model by adjusting visceral fat and brown fat, as well as intestinal flora.